Human molecular evolution since the human-chimpanzee divergence - Pollard, Katherine (Henry Stewart Talks, 2015)
Human-chimpanzee similarities, Human-chimpanzee genomic comparison, DNA duplication in human evolution, DNA substitution in human evolution, Modeling molecular evolution, 2 goals of comparative genomics, Identifying human accelerated regions (HARs)